Adhesive layer, acrylic protective film, preparation method and application thereof

By adding antistatic agents in the adhesive layer by blending and mesoporous silica fiber sustained release method, the existing antistatic acrylic protective film has been solved, and the antistatic performance and high temperature resistance performance are achieved with high efficiency and long-lasting antistatic protection effect.

CN119060660BActive Publication Date: 2025-05-02KUNSHAN BYE MACROMOLECULE MATERIAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411545562.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-05-02
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing anti-static acrylic protective film has poor anti-static properties and high temperature resistance, which are prone to precipitation of anti-static agents due to temperature changes, and fail to properly protect electronic components.

Method used

The adhesive layer is added in two different forms: one is to add antistatic agent through blending to make it float to the surface of the adhesive layer, improve the antistatic effect and enhance the cross-linking density to prevent precipitation; the other is to adsorb the antistatic agent inside the mesoporous silica fiber, and then add the adhesive layer in the form of fibers to achieve the sustained release effect and improve the durability of antistatic properties.

Benefits of technology

It significantly improves the antistatic properties and high temperature resistance of the acrylic protective film, extends the antistatic retention time, and ensures effective protection of electronic components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_5
    Figure SMS_5
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The present invention relates to an adhesive layer, an acrylic protective film, and a preparation method and application thereof, and belongs to the technical field of protective films. The adhesive layer comprises the following components in parts by weight: an acrylate polymer, an antistatic agent A-mesoporous silica fiber composite, an antistatic agent B, a curing agent, and a solvent. The present invention adds the antistatic agent to the adhesive layer in two different forms. One is to add the antistatic agent in a blended manner, with a small amount added, and the antistatic agent floats to the surface of the adhesive layer through the action of the polyether segment, thereby significantly improving the antistatic effect of the adhesive layer; the other addition form is to adsorb the antistatic agent inside the mesoporous silica fiber, and then add it to the adhesive layer in the form of fiber, which can achieve the effect of slow release of the antistatic agent, thereby improving the retention time of the antistatic property, so that the adhesive layer prepared by the present invention has excellent antistatic performance and good antistatic durability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of protective films, and in particular, relates to an adhesive layer, an acrylic protective film, and a preparation method and application thereof. Background Art

[0002] Electronic components are very likely to generate static electricity due to friction during the die-cutting process and transportation, causing a large amount of dust to be adsorbed on the surface of the electronic components, resulting in a decline in product quality and malfunction of some parts. Currently, in the protection of electronic product screens, the conventional acrylic protective film is generally formed by coating an acrylic adhesive on the surface of a PET film, and after curing, a release film is attached to the surface of the acrylic adhesive. It has good transparency, antistatic properties, optical stability and weather resistance. However, the antistatic performance and high temperature resistance of the antistatic acrylic protective film in the prior art are not good. Electronic products are easily affected by temperature during use and transportation. There is a problem of antistatic agent precipitation, which makes the antistatic acrylic protective film unable to be used normally, thereby failing to protect the electronic components well. Therefore, it is necessary to provide an acrylic protective film that can solve the above problems. Summary of the invention

[0003] The object of the present invention is to provide an adhesive layer, an acrylic protective film, and a preparation method and application thereof, wherein an antistatic agent is added to the adhesive layer in two different forms, one of which is to add the antistatic agent in a blended manner, and the antistatic agent is floated to the surface of the adhesive layer through the action of the polyether segment, thereby significantly improving the antistatic effect of the adhesive layer; at the same time, the crosslinking density of the adhesive layer is increased to avoid precipitation of the antistatic agent that floats to the surface of the adhesive layer; another addition form is to adsorb the antistatic agent inside the mesoporous silica fiber, and then add it to the adhesive layer in the form of fiber, which can achieve the effect of slow release of the antistatic agent, thereby improving the retention time of the antistatic property. Thus, the prepared acrylic protective film has excellent antistatic performance and good antistatic durability.

[0004] The technical problem to be solved by the present invention is as follows: the antistatic performance and high temperature resistance of the antistatic acrylic protective film in the prior art are poor, electronic products are easily affected by temperature during use and transportation, and there is a problem of antistatic agent precipitation, which causes the antistatic acrylic protective film to be unable to be used normally, thereby failing to provide good protection for electronic components.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] In one aspect, the present invention provides an adhesive layer, comprising the following components in parts by weight: an acrylate polymer, an antistatic agent A-mesoporous silica fiber composite, an antistatic agent B, a curing agent, and a solvent.

[0007] Furthermore, the mass ratio of the acrylate polymer, the antistatic agent A-mesoporous silica fiber composite, the antistatic agent B, the curing agent and the solvent is (30-50):(6-15):(0.3-0.8):(1.2-4.5):(45-80).

[0008] Furthermore, the acrylate polymer is copolymerized by isooctyl acrylate, methyl methacrylate, acrylic acid, hydroxypropyl acrylate and polyether monomers.

[0009] Furthermore, the mass ratio of isooctyl acrylate, methyl methacrylate, acrylic acid, hydroxypropyl acrylate and polyether monomer is (70-80):(3-5):(0.5-1.5):(0.1-0.5):(2-6).

[0010] Furthermore, the polyether monomer is represented by the following formula (I).

[0011] (I);

[0012] Wherein, R is hydrogen, methyl or ethyl, n=1-10, m=1-4.

[0013] Furthermore, the preparation method of the acrylic acid ester polymer specifically comprises the following steps:

[0014] A1, isooctyl acrylate, methyl methacrylate, acrylic acid, hydroxypropyl acrylate and polyether monomer are mixed uniformly to obtain a mixed monomer;

[0015] A2. Add ethyl acetate and acetone into a reaction kettle, introduce nitrogen, heat to 60-70°C, add two-thirds of the mixed monomer, keep warm for 10-15 minutes, add two-thirds of the initiator, keep warm for 30 minutes, then add the remaining amount of the mixed monomer and initiator, keep warm at 80°C for 3 hours, and obtain an acrylate polymer.

[0016] Furthermore, in step A2, the mass ratio of the mixed monomer, ethyl acetate, acetone and initiator is (50-70): (70-100): (20-35): (0.075-0.15).

[0017] Furthermore, in step A2, the initiator is dibenzoyl peroxide.

[0018] Furthermore, the preparation method of the antistatic agent A-mesoporous silica fiber composite comprises the following steps:

[0019] S1. Add surfactant, potassium chloride and anhydrous ethanol to a hydrochloric acid aqueous solution, stir and dissolve, add tetraethyl orthosilicate, stir at 30-45°C for 20-30 minutes, then stand for 20-25 hours, and then hydrothermally treat at 100-120°C for 24-36 hours. After the hydrothermal treatment, take out the reaction product, cool, filter and dry it, then heat it to 510-560°C at a heating rate of 1-3°C / min and calcine it at high temperature for 6-10 hours to obtain mesoporous silica fiber;

[0020] Furthermore, in step S1, the concentration of the aqueous hydrochloric acid solution is 1-2 mol / L.

[0021] Furthermore, in step S1, the mass ratio of the surfactant, potassium chloride, anhydrous ethanol, aqueous hydrochloric acid solution and tetraethyl orthosilicate is (4-6): (35-38): (10-14): (450-550): (30-36).

[0022] Furthermore, in step S1, the surfactant is hexadecyltrimethylammonium chloride.

[0023] Furthermore, in step S1, the length of the mesoporous silica fiber is 200-500 μm.

[0024] S2, dissolving the antistatic agent A in ethyl acetate, adding mesoporous silica fibers, stirring for 15 minutes, and then ultrasonically dispersing for 30-40 minutes, filtering, washing, and drying to obtain mesoporous silica fibers adsorbed with the antistatic agent A;

[0025] Furthermore, in step S2, the mass ratio of antistatic agent A, ethyl acetate and mesoporous silica fiber is (25-30):(120-140):(8-15).

[0026] S3. Ultrasonic dispersion of the mesoporous silica fiber adsorbed with the antistatic agent A in ethanol, and then adding a silane coupling agent, stirring and reacting at 60-80° C. for 4-10 hours. After the reaction is completed, centrifugation, washing, and drying are performed in sequence to obtain an antistatic agent A-mesoporous silica fiber composite.

[0027] Furthermore, in step S3, the mass ratio of the mesoporous silica fiber adsorbed with the antistatic agent A, ethanol and the silane coupling agent is (2-3): (25-40): (1-1.6).

[0028] Furthermore, in step S3, the silane coupling agent is a mixture of an epoxy silane coupling agent and a vinyl silane coupling agent; the mass ratio of the epoxy silane coupling agent to the vinyl silane coupling agent is (1-2): (1).

[0029] Further, in step S3, the epoxysilane coupling agent includes at least one of 3-(2,3-epoxypropyloxy)propyltrimethoxysilane, 3-(2,3-epoxypropyloxy)propyltriethoxysilane, 3-(2,3-epoxypropyloxy)propylmethyldiethoxysilane, 3-(2,3-epoxypropyloxy)propylmethyldimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyltriethoxysilane, 2-(3,4-epoxycyclohexyl)ethylmethyldiethoxysilane and 2-(3,4-epoxycyclohexyl)ethylmethyldimethoxysilane.

[0030] Furthermore, in step S3, the vinyl silane coupling agent includes at least one of vinyl trimethoxy silane, vinyl triethoxy silane, γ-methacryloxypropyl trimethoxy silane, and vinyl tri(2-methoxyethoxy) silane.

[0031] Furthermore, the antistatic agent A or the antistatic agent B is at least one of 1-ethyl-3-methylimidazole ethyl sulfate, trihydroxyethylmethylamine methyl sulfate, tri-n-butylmethylammonium bis(trifluoromethanesulfonyl)imide, and stearamidopropyl dimethyl-β-hydroxyethyl quaternary ammonium nitrate; the antistatic agent A and the antistatic agent B may be the same or different.

[0032] Furthermore, the curing agent includes at least one of a diisocyanate compound, a triisocyanate compound, and a polyisocyanate compound.

[0033] Further, the solvent includes at least one of ethyl acetate, butyl acetate, butanone, acetone, N,N-dimethylformamide and toluene.

[0034] On the other hand, the present invention also provides an acrylic protective film, comprising a PET substrate layer, an adhesive layer and a release film layer; one side of the PET substrate layer is coated with the adhesive layer, and the side of the adhesive layer away from the PET substrate layer is adhered to the release film layer.

[0035] Furthermore, the release film used in the release film layer is a PET release film.

[0036] On the other hand, the present invention also provides a method for preparing an acrylic protective film, comprising the following steps:

[0037] B1, adding an acrylate polymer to a solvent, then adding an antistatic agent B, stirring evenly, then sequentially adding an antistatic agent A-mesoporous silica fiber composite and a curing agent, and mixing thoroughly to obtain a coating solution;

[0038] B2. Apply the coating liquid on the PET substrate, heat and cure it to obtain an adhesive layer, and cover the surface of the adhesive layer with a release film layer to obtain an acrylic protective film.

[0039] The present invention adds the antistatic agent to the adhesive layer in two different forms. One is to add the antistatic agent in a blended manner, with a small amount added. The antistatic agent is floated to the surface of the adhesive layer through the action of the polyether segment, thereby significantly improving the antistatic effect of the adhesive layer; at the same time, the crosslinking density of the adhesive layer is increased to avoid the precipitation of the antistatic agent floating to the surface of the adhesive layer; in addition, the amount of antistatic agent added in a blended manner in the present invention is small, which can further avoid the problem of antistatic agent precipitation. Another form of addition is to adsorb the antistatic agent inside the mesoporous silica fiber, and then add it to the adhesive layer in the form of fiber, which can achieve the effect of slow release of the antistatic agent, thereby improving the retention time of the antistatic property; at the same time, the mesoporous silica fiber can be interspersed in the crosslinked network of the acrylic ester polymer, thereby increasing the crosslinking density of the adhesive layer, and the high temperature resistance of the adhesive layer is also improved. Thus, the adhesive layer prepared by the present invention has excellent antistatic performance and good antistatic persistence.

[0040] On the other hand, the present invention also provides application of the acrylic protective film prepared above on the screen of electronic products.

[0041] Beneficial effects of the present invention:

[0042] (1) In the technical solution of the present invention, the prepared acrylate polymer is prepared by copolymerization of isooctyl acrylate, methyl methacrylate, acrylic acid, hydroxypropyl acrylate and polyether monomers, wherein the polyether monomer contains a polyether segment structure. The polyether segment has excellent flexibility, which can increase the free volume of the molecular segment, reduce friction, and thus reduce the generation of static electricity. At the same time, it can also promote the antistatic agent to float to the surface of the adhesive layer, thereby significantly improving the antistatic effect of the adhesive layer. The hygroscopicity of the polyether segment also further improves the antistatic property of the adhesive layer.

[0043] (2) In the technical solution of the present invention, the antistatic agent A is adsorbed inside the mesoporous silica fiber and then added to the adhesive layer in the form of fibers, which can achieve the effect of slow release of the antistatic agent, thereby increasing the retention time of the antistatic property.

[0044] (3) In the technical solution of the present invention, the prepared antistatic agent A-mesoporous silica fiber composite can be interspersed in the cross-linked network of the acrylate polymer, so that the high temperature resistance of the adhesive layer is improved. At the same time, the surface of the mesoporous silica fiber is grafted with a silane coupling agent containing epoxy groups and vinyl groups, so that the antistatic agent A-mesoporous silica fiber composite is grafted on the molecular chain of the acrylate polymer, thereby improving the compatibility of the antistatic agent A-mesoporous silica fiber composite and the acrylate polymer. In addition, the introduction of epoxy groups and vinyl groups on the surface of the antistatic agent A-mesoporous silica fiber can increase the cross-linking density of the adhesive layer, thereby avoiding the precipitation of the antistatic agent floating to the surface of the adhesive layer.

[0045] (4) In the technical solution of the present invention, the antistatic agent is added to the adhesive layer in two different forms, so that the acrylic protective film has excellent antistatic properties and good antistatic durability. DETAILED DESCRIPTION

[0046] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0047] Embodiment 1:

[0048] This embodiment provides a method for preparing an antistatic agent A-mesoporous silica fiber composite, comprising the following steps:

[0049] S1. Add 8 g of hexadecyltrimethylammonium chloride, 70 g of potassium chloride and 20 g of anhydrous ethanol to 900 g of a 1 mol / L hydrochloric acid aqueous solution, stir and dissolve, then add 60 g of tetraethyl orthosilicate, stir at 30°C for 20 min and then stand for 20 h, then hydrothermally treat at 100°C for 24 h, take out the reaction product after the hydrothermal treatment, cool, filter and dry, then heat to 510°C at a heating rate of 1°C / min and calcine at high temperature for 6 h to obtain mesoporous silica fibers, the average length of the mesoporous silica fibers is 218 μm;

[0050] S2, dissolving 25g of antistatic agent A in 120g of ethyl acetate, adding 8g of mesoporous silica fiber, stirring for 15min and then ultrasonically dispersing for 30min, filtering, washing and drying to obtain mesoporous silica fiber adsorbed with antistatic agent A;

[0051] S3. Ultrasonic disperse 20 g of mesoporous silica fiber adsorbed with antistatic agent A in 250 g of 90% ethanol, then add 5 g of 3-(2,3-epoxypropoxy)propyltrimethoxysilane and 5 g of vinyltrimethoxysilane, stir and react at 60°C for 4 h. After the reaction, centrifuge, wash and dry in sequence to obtain an antistatic agent A-mesoporous silica fiber composite.

[0052] Embodiment 2:

[0053] This embodiment provides a method for preparing an antistatic agent A-mesoporous silica fiber composite, comprising the following steps:

[0054] S1. Add 10 g of hexadecyltrimethylammonium chloride, 73 g of potassium chloride and 25 g of anhydrous ethanol to 1000 g of a 2 mol / L hydrochloric acid aqueous solution, stir and dissolve, then add 67 g of tetraethyl orthosilicate, stir at 35°C for 25 min and then stand for 23 h, then hydrothermally treat at 110°C for 30 h, take out the reaction product after the hydrothermal treatment, cool, filter and dry, then heat to 530°C at a heating rate of 2°C / min and calcine at high temperature for 8 h to obtain mesoporous silica fibers, the average length of the mesoporous silica fibers is 374 μm;

[0055] S2, dissolving 27g of antistatic agent A in 132g of ethyl acetate, adding 13g of mesoporous silica fiber, stirring for 15min and then ultrasonically dispersing for 35min, filtering, washing and drying to obtain mesoporous silica fiber adsorbed with antistatic agent A;

[0056] S3. Ultrasonic disperse 26 g of mesoporous silica fiber adsorbed with antistatic agent A in 330 g of 90% ethanol, then add 8.4 g of 3-(2,3-epoxypropoxy)propyltriethoxysilane and 5.6 g of vinyltriethoxysilane, and stir the reaction at 70°C for 6 h. After the reaction, centrifuge, wash and dry in sequence to obtain an antistatic agent A-mesoporous silica fiber composite.

[0057] Comparative Example 1:

[0058] Compared with Example 2, step S3 was not performed in Comparative Example 1, and other steps and raw materials were the same as those in Example 2.

[0059] Comparative Example 2:

[0060] Compared with Example 2, the silane coupling agent added in step S3 of Comparative Example 2 is vinyltriethoxysilane, and the other steps and raw materials are the same as those of Example 2.

[0061] Embodiment 3:

[0062] This embodiment provides a method for preparing an antistatic agent A-mesoporous silica fiber composite, comprising the following steps:

[0063] S1. Add 12g of hexadecyltrimethylammonium chloride, 76g of potassium chloride and 28g of anhydrous ethanol to 1100g of 2mol / L hydrochloric acid aqueous solution, stir and dissolve, then add 72g of tetraethyl orthosilicate, stir at -45°C for 20min and then stand for 24h, then hydrothermally treat at 120°C for 28h, take out the reaction product after the hydrothermal treatment, cool, filter and dry, then heat to 560°C at a heating rate of 3°C / min and calcine at high temperature for 10h to obtain mesoporous silica fiber, the average length of the mesoporous silica fiber is 460μm;

[0064] S2, dissolving 30 g of antistatic agent A in 140 g of ethyl acetate, adding 15 g of mesoporous silica fiber, stirring for 15 min and then ultrasonically dispersing for 40 min, filtering, washing and drying to obtain mesoporous silica fiber adsorbed with antistatic agent A;

[0065] S3. Ultrasonic disperse 30 g of mesoporous silica fiber adsorbed with antistatic agent A in 400 g of 90% ethanol, then add 10 g of 3-(2,3-epoxypropoxy)propylmethyldiethoxysilane and 6 g of γ-methacryloxypropyltrimethoxysilane, and stir the mixture at 80°C for 10 h. After the reaction, centrifuge, wash and dry the mixture in sequence to obtain an antistatic agent A-mesoporous silica fiber composite.

[0066] Embodiment 4:

[0067] This embodiment provides a method for preparing an acrylate polymer, which specifically includes the following steps:

[0068] A1, 70g of isooctyl acrylate, 5g of methyl methacrylate, 0.5g of acrylic acid, 0.1g of hydroxypropyl acrylate and 2g of polyether monomer were mixed to obtain a mixed monomer;

[0069] The structural formula of the polyether monomer is shown below:

[0070] ;

[0071] Among them, R is hydrogen, n=2, m=2.

[0072] A2. Add 70 g of ethyl acetate and 20 g of acetone into a reactor, introduce nitrogen, heat to 60°C, add 34 g of mixed monomer, keep warm for 10 min, add 0.05 g of dibenzoyl peroxide, keep warm for 30 min, then add 17 g of mixed monomer and 0.025 g of dibenzoyl peroxide, keep warm at 80°C for 3 h, and obtain an acrylate polymer.

[0073] Embodiment 5:

[0074] This embodiment provides a method for preparing an acrylate polymer, which specifically includes the following steps:

[0075] A1, 75g of isooctyl acrylate, 4.2g of methyl methacrylate, 1g of acrylic acid, 0.35g of hydroxypropyl acrylate and 4g of polyether monomer were mixed to obtain a mixed monomer;

[0076] The structural formula of the polyether monomer is shown below:

[0077] ;

[0078] Among them, R is methyl, n=5, m=2.

[0079] A2. Add 60 g of ethyl acetate and 30 g of acetone into a reactor, introduce nitrogen, heat to 65°C, add 40 g of mixed monomer, keep warm for 15 min, add 0.08 g of dibenzoyl peroxide, keep warm for 30 min, then add 20 g of mixed monomer and 0.04 g of dibenzoyl peroxide, keep warm at 80°C for 3 h, and obtain an acrylate polymer.

[0080] Comparative Example 3:

[0081] Compared with Example 5, no polyether monomer was added in Comparative Example 3, and other steps and raw materials were the same as those in Example 5.

[0082] Embodiment 6:

[0083] This embodiment provides a method for preparing an acrylate polymer, which specifically includes the following steps:

[0084] A1, 80g of isooctyl acrylate, 3g of methyl methacrylate, 1.5g of acrylic acid, 0.5g of hydroxypropyl acrylate and 6g of polyether monomer were mixed to obtain a mixed monomer;

[0085] The structural formula of the polyether monomer is shown below:

[0086] ;

[0087] Among them, R is ethyl, n=5, m=4.

[0088] A2. Add 95 g of ethyl acetate and 25 g of acetone into a reactor, introduce nitrogen, heat to 70°C, add 46.7 g of mixed monomer, keep warm for 15 min, add 0.1 g of dibenzoyl peroxide, keep warm for 30 min, then add 23.3 g of mixed monomer and 0.05 g of dibenzoyl peroxide, keep warm at 80°C for 3 h, and obtain an acrylate polymer.

[0089] Embodiment 7:

[0090] The present embodiment provides an acrylic protective film, comprising a PET substrate layer, an adhesive layer and a PET release film layer; the PET substrate layer is coated with the adhesive layer on one side, and the release film layer is attached to the side of the adhesive layer away from the PET substrate layer, wherein the thickness of the PET substrate layer is 50 μm, the thickness of the adhesive layer is 12 μm, and the thickness of the PET release film layer is 30 μm.

[0091] The method for preparing the acrylic protective film comprises the following steps:

[0092] B1, add 60g of the acrylate polymer prepared in Example 4 to 90g of ethyl acetate, then add 1.6g of antistatic agent B, stir evenly, then add 12g of the antistatic agent A-mesoporous silica fiber composite prepared in Example 1 and 2.4g of hexamethylene diisocyanate in sequence, mix well, and obtain a coating solution; the antistatic agent A and the antistatic agent B are 1-ethyl-3-methylimidazole ethyl sulfate;

[0093] B2. Apply the coating liquid on the PET substrate, heat and cure it at 110°C for 2 minutes to obtain an adhesive layer, and cover the surface of the adhesive layer with a PET release film layer to obtain an acrylic protective film.

[0094] Embodiment 8:

[0095] The present embodiment provides an acrylic protective film, comprising a PET substrate layer, an adhesive layer and a PET release film layer; the PET substrate layer is coated with the adhesive layer on one side, and the release film layer is attached to the side of the adhesive layer away from the PET substrate layer, wherein the thickness of the PET substrate layer is 50 μm, the thickness of the adhesive layer is 12 μm, and the thickness of the PET release film layer is 30 μm.

[0096] The method for preparing the acrylic protective film comprises the following steps:

[0097] B1, add 80g of the acrylate polymer prepared in Example 5 to 120g of butyl acetate, then add 1.2g of antistatic agent B, stir evenly, then add 21g of the antistatic agent A-mesoporous silica fiber composite prepared in Example 2 and 4.8g of isophorone diisocyanate in sequence, mix well, and obtain a coating solution; the antistatic agent A is 1-ethyl-3-methylimidazole ethyl sulfate, and the antistatic agent B is tri-n-butylmethylammonium bis(trifluoromethanesulfonyl)imide;

[0098] B2. Apply the coating liquid on the PET substrate, heat and cure at 120°C for 2 minutes to obtain an adhesive layer, and cover the surface of the adhesive layer with a PET release film layer to obtain an acrylic protective film.

[0099] Embodiment 9:

[0100] The present embodiment provides an acrylic protective film, comprising a PET substrate layer, an adhesive layer and a PET release film layer; the PET substrate layer is coated with the adhesive layer on one side, and the release film layer is attached to the side of the adhesive layer away from the PET substrate layer, wherein the thickness of the PET substrate layer is 50 μm, the thickness of the adhesive layer is 12 μm, and the thickness of the PET release film layer is 30 μm.

[0101] The method for preparing the acrylic protective film comprises the following steps:

[0102] B1. Add 120 g of the acrylic acid ester polymer prepared in Example 6 to 130 g of ethyl acetate and 30 g of acetone, then add 0.6 g of antistatic agent B, stir evenly, then add 30 g of the antistatic agent A-mesoporous silica fiber composite prepared in Example 3 and 9 g of toluene diisocyanate in sequence, mix well, and obtain a coating solution; the antistatic agent A is 1-ethyl-3-methylimidazole ethyl sulfate, and the antistatic agent B is stearamidopropyl dimethyl-β-hydroxyethyl quaternary ammonium nitrate;

[0103] B2. Apply the coating liquid on the PET substrate, heat and cure at 130°C for 1 min to obtain an adhesive layer, and cover the surface of the adhesive layer with a PET release film layer to obtain an acrylic protective film.

[0104] Comparative Example 4:

[0105] Compared with Example 8, in Comparative Example 4, the antistatic agent A-mesoporous silica fiber composite is replaced by the substance prepared in Comparative Example 1, and the other steps and raw materials are the same as those in Example 8.

[0106] Comparative Example 5:

[0107] Compared with Example 8, in Comparative Example 5, the antistatic agent A-mesoporous silica fiber composite is replaced by the substance prepared in Comparative Example 2, and the other steps and raw materials are the same as those in Example 8.

[0108] Comparative Example 6:

[0109] Compared with Example 8, in Comparative Example 6, the antistatic agent A-mesoporous silica fiber composite is replaced by antistatic agent A, and the other steps and raw materials are the same as those in Example 8.

[0110] Comparative Example 7:

[0111] Compared with Example 8, in Comparative Example 7, the acrylic acid ester polymer is replaced by the substance obtained in Comparative Example 3, and the other steps and raw materials are the same as those in Example 8.

[0112] Performance testing:

[0113] The acrylic protective films prepared in Examples 7-9 and Comparative Examples 4-7 were subjected to performance testing:

[0114] Light transmittance: Test the light transmittance of acrylic protective film according to standard GB / T 2410-2008; Antistatic test: Use ZC36 resistor meter to test the surface resistance of adhesive layer; High temperature resistance test: Cut the acrylic protective film into samples with a width of 25mm and a length of 150mm, stick them on the steel plate for testing, and the test conditions are 80℃×70%RH×72h.

[0115]

[0116] It can be seen from the data in Table 1 that the acrylic protective film prepared by the present invention has good light transmittance, excellent antistatic performance and good high temperature resistance. It can be seen from the data of Comparative Example 8 and Comparative Example 4 that since the surface of the antistatic agent A-mesoporous silica fiber composite is not grafted with a silane coupling agent containing epoxy groups and vinyl groups, the compatibility of the antistatic agent A-mesoporous silica fiber composite with the acrylate polymer becomes poor, and the crosslinking density of the adhesive layer decreases, resulting in a decrease in the antistatic performance of the adhesive layer, and the high temperature resistance also decreases significantly, and residual glue appears. It can be seen from the data of Comparative Example 8 and Comparative Example 5 that since the surface of the antistatic agent A-mesoporous silica fiber composite is not grafted with a silane coupling agent containing epoxy groups, the crosslinking density of the adhesive layer decreases, the high temperature resistance also decreases, and a slight residual glue appears. It can be seen from the data of Comparative Example 8 and Comparative Example 6 that when the antistatic agent A is added to the acrylate polymer in a blended manner, the antistatic performance of the adhesive layer is increased, but the high temperature resistance decreases, and residual glue appears. By comparing the data of Example 8 and Comparative Example 7, it can be seen that adding polyether monomers to the acrylate polymer promotes the antistatic agent to float to the surface of the adhesive layer, which can significantly improve the antistatic effect of the adhesive layer.

[0117] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0118] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An adhesive layer, characterized in that: The invention comprises the following components in parts by weight: acrylate polymer, antistatic agent A-mesoporous silica fiber composite, antistatic agent B, curing agent, and solvent; The mass ratio of the acrylate polymer, the antistatic agent A-mesoporous silica fiber composite, the antistatic agent B, the curing agent and the solvent is (30-50): (6-15): (0.3-0.8): (1.2-4.5): (45-80); The acrylic acid ester polymer is copolymerized by isooctyl acrylate, methyl methacrylate, acrylic acid, hydroxypropyl acrylate and polyether monomers; The mass ratio of isooctyl acrylate, methyl methacrylate, acrylic acid, hydroxypropyl acrylate and polyether monomer is (70-80): (3-5): (0.5-1.5): (0.1-0.5): (2-6); The preparation method of the antistatic agent A-mesoporous silica fiber composite comprises the following steps: S1. Add surfactant, potassium chloride and anhydrous ethanol to a hydrochloric acid aqueous solution, stir and dissolve, add tetraethyl orthosilicate, stir at 30-45°C for 20-30 minutes, then stand for 20-25 hours, and then hydrothermally treat at 100-120°C for 24-36 hours. After the hydrothermal treatment, take out the reaction product, cool, filter and dry it, then heat it to 510-560°C at a heating rate of 1-3°C / min and calcine it at high temperature for 6-10 hours to obtain mesoporous silica fiber; S2, dissolving the antistatic agent A in ethyl acetate, adding mesoporous silica fibers, stirring for 15 minutes, and then ultrasonically dispersing for 30-40 minutes, filtering, washing, and drying to obtain mesoporous silica fibers adsorbed with the antistatic agent A; S3, ultrasonically dispersing the mesoporous silica fiber adsorbed with the antistatic agent A in ethanol, then adding a silane coupling agent, stirring and reacting at 60-80° C. for 4-10 hours, and after the reaction, centrifuging, washing, and drying in sequence to obtain an antistatic agent A-mesoporous silica fiber composite; In the step S3, the mass ratio of the mesoporous silica fiber adsorbed with the antistatic agent A, ethanol and the silane coupling agent is (2-3): (25-40): (1-1.6); In step S3, the silane coupling agent is a mixture of an epoxy silane coupling agent and a vinyl silane coupling agent; the mass ratio of the epoxy silane coupling agent to the vinyl silane coupling agent is (1-2): (1).

2. The adhesive layer according to claim 1, characterized in that: The polyether monomer is shown in the following formula (I): (Ⅰ); Wherein, R is hydrogen, methyl or ethyl, n=1-10, m=1-4.

3. The adhesive layer according to claim 1, characterized in that: The preparation method of the acrylic acid ester polymer specifically comprises the following steps: A1, isooctyl acrylate, methyl methacrylate, acrylic acid, hydroxypropyl acrylate and polyether monomer are uniformly mixed to obtain a mixed monomer; A2, ethyl acetate and acetone are added to a reaction kettle, nitrogen is introduced, and the reaction kettle is heated to 60-70°C, two-thirds of the mixed monomer is added, and the mixture is kept warm for 10-15 minutes, two-thirds of the initiator is added, and the mixture is kept warm for 30 minutes, and then the remaining amount of the mixed monomer and initiator are added, and the mixture is kept warm at 80°C for 3 hours to obtain an acrylate polymer; In the step A2, the mass ratio of the mixed monomer, ethyl acetate, acetone and initiator is (50-70): (70-100): (20-35): (0.075-0.15).

4. The adhesive layer according to claim 1, characterized in that: In the step S1, the mass ratio of the surfactant, potassium chloride, anhydrous ethanol, aqueous hydrochloric acid solution and tetraethyl orthosilicate is (4-6): (35-38): (10-14): (450-550): (30-36); in the step S2, the mass ratio of the antistatic agent A, ethyl acetate and mesoporous silica fiber is (25-30): (120-140): (8-15).

5. An acrylic protective film, characterized in that: It comprises a PET substrate layer, an adhesive layer and a release film layer; one side of the PET substrate layer is coated with the adhesive layer, and the side of the adhesive layer away from the PET substrate layer is adhered to the release film layer; the adhesive layer is the adhesive layer according to any one of claims 1 to 4.

6. A method for preparing an acrylic protective film according to claim 5, characterized in that: The following steps are involved: B1, adding an acrylate polymer to a solvent, then adding an antistatic agent B, stirring evenly, then sequentially adding an antistatic agent A-mesoporous silica fiber composite and a curing agent, and mixing thoroughly to obtain a coating solution; B2. Apply the coating liquid on the PET substrate, heat and cure it to obtain an adhesive layer, and cover the surface of the adhesive layer with a release film layer to obtain an acrylic protective film.

7. Use of the acrylic protective film as claimed in claim 5 on the screen of an electronic product.

Citation Information

Patent Citations

  • Method for preparing mesoporous silica molecular sieve fiber

    CN101387019A

  • PE (polyurethane) protective film glue and preparation method thereof

    CN102206476A